A swiftly tilting planet - L'Engle, Madeleine (New York : Bantam Doubleday Dell Books for Young Readers, 1981)
The youngest of the Murry children must travel through time and space in a battle against an evil dictator who would destroy the entire universe.
Companion to: A wrinkle in time.
"A Yearling book."
Original copyright: 1978.
Edition statement taken from P. [4] of cover.
RL: 6.4.
010-014.
Keywords: Time travel -- Juvenile fiction; Good and evil -- Juvenile fiction; Time travel -- Fiction; Science fiction